A139 A LOW FODMAP DIET REDUCES SYMPTOMS IN INDIVIDUAL IBS PATIENTS BUT NOT MUCOSAL IMMUNE ACTIVATION OF NOCICEPTORS. (15th March 2019) - Bennet, S M; Tuck, C J; Jiménez-Vargas, N N; Lopez Lopez, C D; Jaramillo Polanco, J O; Morissette, C; Rolland, S; Bercik, P; Reed, D E; Vanner, S
Abstract: Background: Lowering dietary FODMAPs in IBS patients reduces symptom severity in many cases yet the mechanism is poorly understood. It has been proposed that FODMAPs may activate mast cells in some patients. Mast cell mediators in turn could sensitize nociceptors innervating the gut, leading to exaggerated pain signalling. Aims: To determine if altering FODMAP intake modulates the excitability of nociceptors. Methods: Three IBS patients (Rome IV; 12 wk longitudinal crossover study) followed a low- and high-FODMAP diet. Mucosal sigmoid biopsies were collected during sigmoidoscopy and symptoms recorded using the IBS symptom severity score (IBS-SSS) at four 3 week intervals: 1) baseline, 2) after a run-in period and 3, 4) after each dietary intervention period; patients reporting score reductions of ≥50 after intervention were defined as responders. Mouse nociceptive dorsal root ganglia (DRG) neurons were cultured overnight with biopsy supernatants. Excitability of the neurons was assessed using perforated patch-clamp techniques and a decrease in rheobase was equated with increased excitability. Results: Patients 1 and 2 (high FODMAP diet 1 st ) responded only to the low FODMAP diet compared to run-in (Table 1). Patient 3 (low FODMAP diet 1 st ) responded to both diets. Rheobases at the different time points did not differ in any patient (Table 1). The baseline rheobase of the IBS patients did not differ from control supernatants, in contrast to that seen previously with many patients. Conclusions: Low FODMAP dietary intervention reduced symptoms in this patient subset yet colonic biopsy supernatants had no effect on DRG neuron excitability. Thus, this pilot study suggests sigmoid mucosal immune activation may not underlie increased nociceptive signalling in this small subset of IBS patients. Further studies of other IBS patients is needed where baseline immune activation is present as well as studies of other sources of active metabolites e.g. the microbiota. Funding Agencies: CIHR